The impact of user charges on health outcomes in low-income and middle-income countries: a systematic review. (10th January 2019) - Qin, Vicky Mengqi; Hone, Thomas; Millett, Christopher; Moreno-Serra, Rodrigo; McPake, Barbara; Atun, Rifat; Lee, John Tayu
Abstract : Background: User charges are widely used health financing mechanisms in many health systems in low-income and middle-income countries (LMICs) due to insufficient public health spending on health. This study systematically reviews the evidence on the relationship between user charges and health outcomes in LMICs, and explores underlying mechanisms of this relationship. Methods: Published studies were identified via electronic medical, public health, health services and economics databases from 1990 to September 2017. We included studies that evaluated the impact of user charges on health in LMICs using randomised control trial (RCT) or quasi-experimental (QE) study designs. Study quality was assessed using Cochrane Risk of Bias and Risk of Bias in Non-Randomized Studies—of Intervention for RCT and QE studies, respectively. Results: We identified 17 studies from 12 countries (five upper-middle income countries, five lower-middle income countries and two low-income countries) that met our selection criteria. The findings suggested a modest relationship between reduction in user charges and improvements in health outcomes, but this depended on health outcomes measured, the populations studied, study quality and policy settings. The relationship between reduced user charges and improved health outcomes was more evident in studies focusing on children and lower-income populations. Studies examining infectious disease–related outcomes, chronic disease management and nutritional outcomes were too few to draw meaningful conclusions. Improved access to healthcare as a result of reduction in out-of-pocket expenditure was identified as the possible causal pathway for improved health. Conclusions: Reduced user charges were associated with improved health outcomes, particularly for lower-income groups and children in LMICs. Accelerating progress towards universal health coverage through prepayment mechanisms such as taxation and insurance can lead to improved health outcomes and reduced health inequalities in LMICs. Trial registration number: CRD 42017054737.